Novel 2-(5-Arylthiophen-2-yl)-benzoazole Cyclometalated Iridium(III) dppz Complexes Exhibit Selective Phototoxicity in Cancer Cells by Lysosomal Damage and Oncosis - Kasparkova, Jana; Hernández-García, Alba; Kostrhunova, Hana; Goicuría, Marta; Novohradsky, Vojtěch; Bautista, Delia; Markova, Lenka; Santana, María Dolores; Brabec, Viktor; Ruiz, José (Journal of medicinal chemistry, 2024)
A second-generation series of biscyclometalated 2-(5-aryl-thienyl)-benzimidazole and -benzothiazole Ir(III) dppz complexes [Ir(C^N)2(dppz)]+, Ir1-Ir4, were rationally designed and synthesized, where the aryl group attached to the thienyl ring was p-CF3C6H4 or p-Me2NC6H4. These new Ir(III) complexes were assessed as photosensitizers to explore the structure-activity correlations for their potential use in biocompatible anticancer photodynamic therapy. When irradiated with blue light, the complexes exhibited high selective potency across several cancer cell lines predisposed to photodynamic therapy; the benzothiazole derivatives (Ir1 and Ir2) were the best performers, Ir2 being also activatable with green or red light. Notably, when irradiated, the complexes induced leakage of lysosomal content into the cytoplasm of HeLa cancer cells and induced oncosis-like cell death. The capability of the new Ir complexes to photoinduce cell death in 3D HeLa spheroids has also been demonstrated. The investigated Ir complexes can also catalytically photo-oxidate NADH and photogenerate 1O2 and/or •OH in cell-free media.
Keywords: Benzothiazoles; Lysosomes; Cell Line, Tumor; lyzozomy; Neoplasms; benzothiazoly; nádory; lidé; Antineoplastic Agents; protinádorové látky; komplexní sloučeniny; iridium; Photosensitizing Agents; fototoxická dermatitida; Dermatitis, Phototoxic; Iridium; fotosenzibilizující látky; Coordination Complexes; nádorové buněčné linie; Humans